Concentration of Asprosin Associated with Poor Control of Type 2 Diabetes Mellitus in Diyala Province - Alaa Abed Mahmoud; Walaa Ismael Jassim; Ahmed Abdul Hussein Mohsin; Ahmed M. Senan (Journal of Techniques)
A newly secreted adipokine called asprosin is brought on by fasting as well as encourages hepatic glucose release. Its loss of function through immunologic or genetic methods has a significant effect on lowering glucose and insulin as a result of decreased hepatic glucose release. This study aimed to measure the level of asprosin in a group of poor control hyperglycemic patients and compare its level with the control group and find its correlation with obesity and lipid profile. Asprosin level in serum was assessed by enzyme-linked immunosorbent assay (ELISA) technique for 110 Iraqi patients with type 2 diabetes mellitus(T2DM), as well as 70 individual healthy controls. Percentage of glycated hemoglobin (HbAIc), fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL) and low-density lipoprotein (LDL) concentration were calculated using Roche cobas integra 400 plus. Patients with type 2 diabetes mellitus reported increased levels of asprosin in their blood when compared with controls (p < 0.001). A significant positive correlation was seen between asprosin and FBG in patient’s (P< 0.05). Non-significant correlation was seen between asprosin and body mass index (BMI) or lipid profile. In conclusion, according to the asprosin level in serum, there was a highly significant difference between patients with type 2 diabetes mellitus and control group. BMI and lipid abnormalities were not correlated to asprosin level in the serum of patients.